Should microcirculation monitoring be used to guide fluid resuscitation in severe sepsis and septic shock? (2015)
Tissue hypoperfusion and subsequent limited oxygen transport are critical features conducting to organ failure during shock states. Therefore, early identification of tissue hypoperfusion and adequate resuscitation are key for improving the probability of survival after septic shock. (1,2) However, how to identify organ perfusion abnormalities at the bedside and select the type and amount of fluids required to improve tissue hypoxia remain highly controversial. Traditionally, clinical signs, such as reduced blood pressure and urinary output, altered consciousness, and mottled skin, have been used to identify tissue perfusion abnormalities.